What if... we Knew the Effects and Benefits of Virtual Reality in Childhood? - de Araújo, Calíope Corrêa; Kunst, Marina Holanda; Uehara, Misa; Peres, Fabiana Frata Furlan; Teixeira, João Marcelo X. N. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
This article provides a systematic review of Head-Mounted Display Virtual Reality devices intended for children. The primary objective of this study is to investigate inquiries concerning the safe utilization of HMD devices for children, potential associated risks, and the recommended age group for usage. By examining the impacts, advantages, and obstacles associated with the exploration of this emergent technology, this research strives to amalgamate findings on the repercussions of HMDs on children’s physical, cognitive, learning, and safety well-being. It offers pertinent insights for the safe administration of this technology to children across various age groups. The review encompassed 59 research articles conducted in various countries, which highlighted both the positive effects, such as the reduction of anxiety and improvement of social skills, and the negative effects, such as physical discomfort and fatigue, associated with prolonged HMD use. Finally, the analysis included a comparison of different device models and exposure times, offering a comprehensive overview of best practices and recommendations for future studies.